Investigation and Analysis of Technostress among Teacher at Higher Secondary Level - Dr.A .Catherin Jayanthy, N. Annalakshmi (International Journal of Advanced Science and Technology, 2019)
The technology has played major roles in all fields especially in education.  The information and communication technology (ICT) in education is to enhance, support and delivered the information in worldwide.  .  The technology has develop into a integral part in teaching and learning practices.  Now-a-days, many schools are replacing with interactive digital board, whiteboard, and they use smartboard for developing or creating good learning environment for students. Some of them feel stress or feel depression when they are using technology overtime. The technostress is the negative psychological effects between the person and introduction of innovative technology.  The individual or people are experienced technostress since they can't ready to regulate the technology overtime.  The main objective of this study was to find out the level of technostress among teachers.  This paper is to analyze the factors of causing technostress among teacher in schools.  The data was collected from 200 teachers from Madurai District.  The descriptive survey method was adopted for this present study.  Further, this paper also discussed about the various coping strategies of reducing stress, how to promote positive outlook about technology and also to give strategies to use it user friendly. Keyword:. Techno-Stress, Factors, Dimension, Coping Strategies